2009
DOI: 10.1111/j.1744-7402.2009.02425.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Double-Layer Structure LTCC Substrate with Enhanced Flexural and Adhesions Strengths

Abstract: To enhance both adhesive strength and flexural strength, a new structure consisting of two layers with different degree of crystallization was investigated as a substrate material for low‐temperature co‐fired ceramics (LTCC). A mixture system of silica‐based glass and Al2O3 crystalline powder, which is known to be crystallized during the sintering process was used. Glasses with different compositions and various amounts of alumina filler were used for our new structure. Crystallization behavior was monitored b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Shang et al [24] added a small amount of CaO to a K 2 O-B 2 O 3 -SiO 2 -Al 2 O 3 glass to improve the material densification and obtained a glass-ceramic with flexural strength of 173 MPa. For glass/ceramic system of LTCC materials, studies have shown that a CaO-B 2 O 3 -SiO 2 / Mg 2 Al 4 Si 5 O 18 [25], CaO- [26] system glass sintering will react to form a strong phase interface, which is conducive to the wettability of the glass to the ceramic filler and improves the densification of the materials, and the formed anorthite phase can also improve the flexural strength. The CaO content of the glass in these studies was generally high (> 35 wt.…”
Section: Introductionmentioning
confidence: 99%
“…Shang et al [24] added a small amount of CaO to a K 2 O-B 2 O 3 -SiO 2 -Al 2 O 3 glass to improve the material densification and obtained a glass-ceramic with flexural strength of 173 MPa. For glass/ceramic system of LTCC materials, studies have shown that a CaO-B 2 O 3 -SiO 2 / Mg 2 Al 4 Si 5 O 18 [25], CaO- [26] system glass sintering will react to form a strong phase interface, which is conducive to the wettability of the glass to the ceramic filler and improves the densification of the materials, and the formed anorthite phase can also improve the flexural strength. The CaO content of the glass in these studies was generally high (> 35 wt.…”
Section: Introductionmentioning
confidence: 99%